Efficient conversion from UV light to near-IR emission in Yb3+-doped triple-layered perovskite CaLaNb3O10. (April 2015) - Lu, Yuting; Li, Yuze; Qin, Lin; Huang, Yanlin; Qin, Chuanxiang; Tsuboi, Taiju; Huang, Wei
Graphical abstract: CaRNb3 O10 is a self-activated oxide due to charge transfer transition in octahedral NbO6 groups. CaLaNb3 O10 :Yb 3+ presents intense IR emission due to the cooperative energy transfer from host (NbO6 ) to Yb 3+ is responsible. It could be expected to be potentially applicable for enhancing photovoltaic conversion efficiency of Si-based solar cells. Abstract: Yb 3+ -doped triple-layered perovskite CaLaNb3 O10 micro-particles were synthesized via the solid-state reaction method. The crystal structure and morphology of the polycrystalline samples were investigated by X-ray powder diffraction (XRD) and scanning electron microscopy (SEM) measurements, respectively. The reflectance spectra, photoluminescence (PL) excitation and emission spectra, the decay curves, and the absolute quantum efficiency (QE) of the near-infrared (NIR) emission (910–1100 nm) were measured. Under excitation of UV light, Yb 3+ -doped perovskite shows an intense NIR emission attributed to the 2 F5/2 → 2 F7/2 transitions of Yb 3+ ions, which could match maximum spectral response of a Si-based solar cell. This is beneficial for its possible application in an enhancement of the photovoltaic conversion efficiency of solar energy utilization. The efficient energy transfer in Yb 3+ -doped CaLaNb3 O10 from NbO6 groups into Yb 3+ ions was confirmed by the spectra and fluorescent decay measurements. Cooperative energy transfer (CET) was supposed to be the NIR emission mechanism.